Analysis of Crisis Management Measures in the War Period as a Prerequisite for the Sustainable Development of Ukraine’s Industry - Gibadullin, Oleksiy; Latynin, Mykola; Kosenko, Alisa; Fesak, Serhii (Pressing Problems of Public Administration, 2024)
This article focuses for the first time on the importance of an analytical approach to building a sustainable industrial recovery system based on a clear and transparent industrial policy aimed at efficient and transparent public-private partnership in a joint project. The goal of the article is to provide a scientific-analytical justification for the vector of building and developing the industrial recovery management system in Ukrainian regions and identifying «points of contact» in public-private partnerships and inter-sectoral interaction as the basis of regenerative processes during the period of martial law and after hostilities. The authors note that one of the key elements in the process of forming a sustainable industrial recovery system is the understanding of the importance of building a management system for industrial recovery of regions on the principles of public-private partnership and creating a business climate conducive to regenerative processes, considering the joint balance of interests between the state and business. This requires a broad comprehensive approach that combines an analysis of pre-war institutional development problems of the industrial economy, the current state of relations between the state and business, and identifies the most optimal model for implementing public-private partnership practices, considering the joint interest. It is important to take into account, first and foremost, the balanced equilibrium between the business demand and the capabilities of the state, and the underutilized intangible potential created on the basis of mutual trust and capable of facilitating regenerative processes «here and now» during the ongoing active hostilities, as well as guaranteeing the achievement of sustainable development goals in the future. As of now, it can be stated with certainty that the main request from the business is the creation of a business environment conducive to the development of recovery processes (from overcoming corruption risks, opacity, and pressure from the state, to a certain protectionism of the domestic manufacturer, as the economic component of sustainable development goals). The article reveals the cause-and-effect relationships and common «points of contact» for reviewing approaches to public-private partnership and management processes of the sustainable industrial recovery system during the period of martial law and after Victory as a prerequisite for post-war recovery and sustainable development of regions, which is a basic condition for searching and implementing ways to optimally use the available management resource, overcoming technological gaps, and creating conditions for the return of qualified migrants to Ukraine.